Implementasi Algoritma Exclusive OR (XOR) Dalam Pengembangan Aplikasi Chat Berbasis Android - Pujo Hari Saputro (Jurnal Sistem Informasi dan Teknologi Informasi, 2023)
Android is an operating system that is widely used in this modern era. This is inseparable from Android features which are increasingly being developed to facilitate the user experience. Along with these developments, security issues also arise when exchanging information or data. Security is an important aspect of the development of the modern information technology era, so that a branch of knowledge that studies data security or known as cryptography develops. This study aims to design and build a secure chat application based on Android and implement the XOR algorithm. This algorithm is used to secure information so that it cannot be read before it reaches the recipient. This algorithm calculation produces a random message (ciphertext) that can only be read by the recipient. The result of this search is a chat application in which there is a security feature where the recipient must enter the same key as the sender so that the message can be read. Testing this application is done by sending a message and then entering the same key between the sender and the recipient